Knowledge of genetics and the role of the nurse in genetic health care: a survey of Italian nurses. (31st July 2012) - Godino, Lea; Turchetti, Daniela; Skirton, Heather
Abstract: Aim: To report a study of Italian nurses' understanding of genetics. The objectives were to explore nurses' basic knowledge of genetics, their perceptions of the relevance of genetics and their opinions about the role of the genetic nurse. Background: As the knowledge of the genetic basis for disease has developed, pressure to give genetic healthcare services for a larger number of individuals has increased. Specialist genetic nurses currently work in many countries; however, there are very few specialist genetic nurses in Italy and the preparedness of Italian nurses to give care for people with or at risk for genetic conditions is unclear. Design: A cross‐sectional survey. Methods: The survey was administered over 3 months during 2011. Registered Nurses aged 21–65 years were recruited via the website of the Italian nurse registration body, social network sites, hand‐distributed flyers and email. Three hundred and eight‐five (90%) nurses completed the survey. Data were analysed using descriptive statistics, Kruskal‐Wallis tests for distribution and Spearman's Rho analysis of correlations. Results: The majority of respondents correctly answered at least four of five genetics knowledge questions. There were no statistically significant difference between knowledge scores when analysed according to age, but scores were positively correlated with higher academic qualifications and previous genetics education. A minority of respondents believed genetics was highly relevant to the nursing role. Conclusion: It is essential to ensure that educational provision for nurses includes not only the genetic concepts underpinning health and disease, but also how these are applied to nursing care.